Non-Regular Pseudo-Differential Operators on Matrix Weighted Besov-Triebel-Lizorkin Spaces (Journal of Mathematical Study, 2024)
In this paper we obtain the boundedness of non-regular pseudo-differentialoperators with symbols in Besov spaces on matrix-weighted Besov-Triebel-Lizorkinspaces. These symbols include the classical Hörmander classes.
Keywords: Pseudo-differential operator; matrix weight; Besov space; Triebel-Lizorkin space.